ASSOCIATION BETWEEN ATP1A1 GENE POLYMORPHISMS WITH SEMEN CHARACTERISTICS IN HOLSTEIN BULLS - S. M. Eidan; S. A. Khudhir (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was conducted to identify the polymorphism of ATP1A1 gene, distribution ratios, and its association with semen characteristics of Holstein bulls. Twenty-five Holstein bulls were used currently. Blood samples were collected via venipuncture to separate the DNA and identify the polymorphism of the ATP1A1 gene. Semen was collected using an artificial vagina for fresh evaluation. Results were showed the change of cytosine (C) nucleotide at site 15738 to adenine (A) at the exon 17 (SNP C15738A) of the ATP1A1 gene. Two polymorphisms were obtained according to this change, the first is wild (CC; allele frequency 0.84), and the second is heterogeneous (CA; allele frequency 0.16). The CC polymorphism of the ATP1A1 gene exhibited a highly significant (p<0.01) superiority for ejaculate volume, sperm concentration, and mass activity, and for sperm’s cell individual motility (p<0.05), compared with the CA polymorphism of Holstein bulls. The other semen characteristics did not differ between the two mentioned polymorphisms. This polymorphism exhibited obvious semen characteristics despite stress conditions of feed shortage and poor management practices accompanied with the covid-19 pandemic. This gene can be used to predict the fertility and stress resistance of bulls before they reach sexual maturity and its reflection on the economic return of breeding these bulls at the artificial insemination centers.